Underage Marriage in Legal Sociology Review - Vicki Dwi Purnomo; Ahmad Turmudi; Najib A. Gisymar; Rohidin (Jurnal Sosial, Politik dan Budaya (SOSPOLBUD), 2023)
Indonesia is one of the tasks of a country with high underage marriages. This study aims to describe the legal sociology review of underage marriages and to describe the factors that cause underage marriages. This study examines further the problems that occur in underage marriages in a sociological review of law. By using a juridical-normative approach with a qualitative research type with a descriptive concept, the data source used is secondary data related to this research. presentation of data based on a theoretical framework. Data collection techniques with literature study. Data analysis techniques with deductive methods. In view of the sociology of underage marriage law there are still many problems, one of which is due to the dispensation provided by the law. Government commitment is needed to reinforce the practice of underage marriages.